(untitled) - Jobin, William R. (London,New York, 1999)
This book provides planners with an overview of a number of global water projects and the unexpected ecological consequences which the engineers encountered or caused. The examples stress human health and aquatic ecology. Through historical assessment of well documented case studies, the book also identifies the steps planners took to overcome these problems, and gives guidance for planners of future projects. The book is suitable for use as an introductory text by young engineers exploring the scope of the profession, and for graduate engineers specializing in design of international water projects or environmental engineering
Keywords: Hydraulic engineering,Hydraulic engineering,Kỹ nghệ thủy lực; Environmental aspects.,Health aspects